2019
DOI: 10.1093/rpd/ncz056
|View full text |Cite
|
Sign up to set email alerts
|

Local DRLS for Paediatric Ct Examinations Based on Size-Specific Dose Estimates in Kermanshah, Iran

Abstract: Due to the radiosensitivity of paediatric patients to X-ray, it is necessary to survey the paediatric DRLs using size-specific dose estimates (SSDE). In the present study, we determined the local diagnostic reference levels (DRLs) for paediatric chest, head and abdomen-pelvis CT examinations and their Surview scans in Kermanshah city, Iran. For ≤1 year, 1–5 years, 5–10 years and 10–15 years the DRLs (mGy) based on SSDE were determined N/A, 6.00, 6.25, 8.27 for abdomen-pelvis, and 8.74, 7.45, 11.15, 10.45 for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…As we mentioned in first paragraph the CT scan is responsible for 49% of all medical exposure; thus, for the first DRLs establishment in Ilam we focused on CT scan as the more important modality in medical radiation exposures. Many studies have established the CT scan DRLs in different countries (9)(10)(11)(12) ; also same studies carried out in Iran (1,7,9,13,14) . Sohrabi et al study is the most greatest study in Iran that was carried out in 157 scanner for assessment the radiation dose of head, sinus, chest, and abdomen-pelvis CT examinations to establishment the national DRLs (15) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we mentioned in first paragraph the CT scan is responsible for 49% of all medical exposure; thus, for the first DRLs establishment in Ilam we focused on CT scan as the more important modality in medical radiation exposures. Many studies have established the CT scan DRLs in different countries (9)(10)(11)(12) ; also same studies carried out in Iran (1,7,9,13,14) . Sohrabi et al study is the most greatest study in Iran that was carried out in 157 scanner for assessment the radiation dose of head, sinus, chest, and abdomen-pelvis CT examinations to establishment the national DRLs (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Today's researchers are interesting to using SSDE index for determining the DRLs in CT examinations (1,3,4) . The SSDE is more accurate than CTDIv for estimation of patient dose considering the patient size (5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since SSDE was announced, several softwares have been developed to measure the effective dose and organ dosage based on SSDE [9,10]. Several studies reported that SSDE was used to represent dose optimization values such as diagnostic reference level (DRL) and acceptable quality dose (AQD) [11][12][13][14]. SSDE is estimated from the output dose or the volume CT dose index (CTDI vol ) and patient characteristics.…”
Section: Introduction mentioning
confidence: 99%
“…At present, the SSDE concept has been widely accepted [7][8][9] and is widely used for various applications, for example for radiation dose surveys [10], dose optimization [11][12][13], establishing diagnostic reference levels (DRL) [14,15], and so on. Various attempts to improve SSDE calculations have been carried out [16,17], and automation of these calculations to make them easier and more effective, are also now available [18,19].…”
Section: Introductionmentioning
confidence: 99%